La tardive floraison des campagnes. L’architecture moderniste des kolkhozes dans l’Estonie soviétique - Mart Kalm (In Situ)
In the second half of the 20th century there was no significant construction in rural Europe, instead it was a period when villages began to decline. Industrialisation, which caused urbanisation and also a surplus of agricultural workers because of industrialisation in agriculture, meant villages began to empty. But Soviet Estonia surprisingly provides an exception to this trend with fervent construction in rural areas. Within the new economic conditions, collective enterprises fairly blossomed in the 1960s and 70s in Estonia. The higher living standards provided by the collective farms even managed to slow down urbanisation, and the new settlement patterns established by the collective farms, along with the infrastructure that developed, helped establish the right conditions for the growth of ambitious modernist architecture. The implementation of the idea of eliminating the differences between the country and the city meant that an urban lifestyle would be established in the country. To achieve the desired conveniences, building homes in the country meant building apartment blocks. The state ruled that everything built in the collective farm centres had to be built according to standardised designs, with one exception. As a single generous gesture the Estonian SSR allowed the collective farm administrative office cum clubhouse to be built according to a one-off design. Thanks to its architecture the main building of the Kurtna Experimental Poultry Farm, built in 1965–66, became famous. In the 1970s the most outstanding designer of rural architecture was Toomas Rein. One that needs mention is his administrative building at Tsooru, in the south eastern corner of Estonia, for the J. Sverdlov collective farm (1969–77). At the end of the 1970s the architects of the Tallinn School turned to postmodernism. The administrative building for Laekvere collective farm (1984–89) designed by Vilen Künnapu, is a prime example of architecture that blends into the surrounding environment and considers the existing traditional urban space.